Association of Serum Vitamin B12 level and Acute Ischaemic Stroke (Bangladesh Journal of Neuroscience, 2026)
Background: Stroke, the second leading cause of death worldwide is a multifactorial disease. Several risk factors had been identified for stroke. Hyperhomocysteinemia is one of the latest additions among the risk factors responsible for ischaemic stroke.Though vitamin B12 is one of the causative factors of hyperhomocyteinemia, very few studies showed a relation between ischaemic stroke and Vitamin B12 deficiency. So, this study aimed to find out the association between vitamin B12 deficiency and acute ischaemic stroke.Methods: This case-control study was conducted at the department of Neurology, Mymensingh Medical College & Hospital. Fifty patients of first ever acute ischemic stroke and 50 apparently healthy controls, matched for age (56.90±9.88 versus 52.88±6.18) and sex (31 male and 19 female) were recruited. Vitamin B12 was measured by Enzyme-linked immunosorbent assay and its status was considered as low, borderline and normal with vitamin B12 levels of